Relation between mean platelet volume and subclinical atherosclerosis in patients with metabolic syndrome - Ali Rıza Gülcan; Mustafa Serkan Karakaş; Barış Akdemir; Mustafa Uçar; Refik Emre Altekin; Hüseyin Yılmaz (KARE Publishing, 2014)
Objectives: Metabolic syndrome (MetS) is associated with increased cardiovascular morbidity and mortality. There is evidence of platelet activation in MetS. Mean platelet volume (MPV), a determinant of platelet activation, is a newly emerging risk factor for atherothrombosis. Therefore, we investigated the possible association between subclinical atherosclerosis, as evaluated by carotid intima-media thickness (CIMT) measurement and MPV, in MetS patients. Study design: Seventy-four patients with MetS were enrolled in the study. Patients were divided into two groups according to CIMT measurement: 35 patients with CIMT ≥1.0 mm were in Group 1 and 39 patients with CIMT <1.0 mm were in Group 2. MPV was measured using an automated blood cell counter. Results: The MPV level was significantly higher in patients with CIMT ≥1.0 mm than in patients with CIMT <1.0 mm (8.2+-0.7 vs. 7.8+-0.6 fl; p=0.01). In our study, we observed that platelet count was lower in KIMK ≥1.0 mm group and this finding was also found to be statistically significant. Conclusion: The risk of atherosclerosis could be shown by following the MPV values in MetS patients. Therefore, our results suggest that MPV is an important marker for early detection of atherosclerotic risk in patients with MetS.